Pengaruh Bentuk Permukaan Piston Rata (Flat) Dan Piston Cembung (Dome) Terhadap Performa Dan Emisi Gas Buang Pada Mesin Sport 200cc - Asroful , Abidin; Noval Defa , Aprifi; Mokh. Hairul, Bahri (Indonesian Journal Publisher, 2024)
The aim of this research is to determine the effect of engine performance (torque and power), as well as exhaust emissions after replacing the piston. Tests were carried out on a 200CC engine with flat piston specifications with a diameter of 65.0 mm and replaced with a convex piston with a diameter of 65.0 mm using pertalite fuel. The research results obtained by replacing the convex piston (dome) caused the volume of the combustion chamber to decrease resulting in increased torque and power. There was an increase in torque of 0.02607 ft-lbs and an increase in power of 41.95384 HP, then the compression ratio increased by 0.5%. In exhaust gas emissions containing CO, HC, O2, CO2 using a gas analyzer with the results of research on flat pistons and dome pistons, it can be seen that emissions from convex pistons (dome) have increased compared to flat pistons. with the highest increase in stationary of 6.17% in CO emission content due to incomplete combustion residue, which means that the type of piston has a significant influence on exhaust gas emissions. Then the exhaust gas emission test results also show an increase in the O2 emission content on the flat piston at RPM 5000 with a value of 4.24% due to the mixture of oxygen and fuel being more perfect, but on the convex piston (dome) there is a significant increase Compared to a flat piston only at RPM 6500 with a value of 4.53% in O2 emission content. The HC and CO2 emissions content shows unstable or changing values. Apart from that, variations in engine speed also affect the exhaust emissions produced.